Automotive component innovation development and diffusion of engine management technologies - Amey, R. G.
Engine management systems (EMS) were studied within three automotive manufacturers with regard to US economy and emissions regulations and consumer demands in the 1970s and 1980s. Case studies of racing and sports car fuel delivery systems are discussed and it is suggested that a new, not extended, product life cycle begins.
In recent years, automobile manufacturers have successfully met, and in many cases exceeded, the apparent incompatibilities between government-imposed economy and emissions regulations, and consumer-oriented durability and performance demands. This paper focuses on the heritage of engine management systems (EMS) by examining the evolution of the fuel delivery systems of the Honda-MacLaren Formula 1 race cars and the Chevrolet Corvette and Nissan Z/ZX production sports cars. These case studies provide the foundation for a modification to the product life-cycle model, merging the seemingly unrelated technologies of automotive fuel and ignition systems and computer microprocessor components. EMS technology includes research and development (R&D), testing, technical assistance and production across an extensive network of generalists and specialists including automakers, race car constructor organizations, and parts suppliers. Breaking from the traditional total vehicle development by a single manufacturer, this division of labor results in more rapid incremental innovation of both the components (the parts) and the automobile (the end product and the sum of the parts). However, while the end product may be only incrementally improved, the parts-in this case, EMS-are so distinctly different that a new - not an extended -product life-cycle beings.
Keywords: Automotive component innovation; Engine management technologies